LECTINOHYSTOCHEMICAL RESEARCH OF COLON IN HUMANS AT NORMAL AND AT NEOPLASTIC PROCESS USING LECTINS SPECIFIC FOR T ANTIGEN AND N-ACETHYLLACTOSAMINE - Antonyuk, R.V.; Луцик, О.Д. (World of Medicine and Biology, 2015)
It is known that in the case of malignant degeneration of colon both carbohydrate and protein parts of mucin are transformated. Carbohydrate and peptide epitopes are more or less sulfated, sialated, shortened and often contain T-antigen. To investigate these changes lectins (substances of protein nature that can selectively bind to carbohydrates, but do not produce their chemical transformations) are often used as molecular probes. In the present paper we studied as lectins were binding with carbohydrate receptors in human colon neoplasia. We used two groups of lectins - specific for T-antigen (PNA, ACA) and specific to the N-acethyllactosamine (RCA, PIFA, CNFA).The aim was to investigate the possibility of using the above mentioned peroxidase-labeled lectins for the diagnosis of neoplastic degeneration in humans in the case of colon cancer of varying degrees of differentiation.Intraoperational and biopsy material of 28 cases of colon cancer have been investigated: (highly differentiated adenocarcinoma – 14, moderate tumor differentiation - 10, and poorly differentiation - 4, in three samples mucinous carcinomas structure morphology contained). 4 cases of colon adenomas, and 9 samples of autopsy material human colon without signs of disease have been investigated as well. As a result of the research, it was found that PNA, RCA, CNFA carbohydrate determinants in normal mucosa epitheliocytes of colon virtually were absent, though still in some sections not intense coloration was observed. Whereas lectin-positive epithelial cells to ASA, the PIFA were found in almost all samples.All used lectins showed selectivity to cytoreceptors of colon tumors. Both, PNA, CNFA were able to selectively interact with carbohydrate determinants incorpotated in neoplasy of colon cancer. Percentage of lectin-positive histological samples using these two lectins almost coincide. of It reached 83% for PNA and 80 % for CNFA in carcinoma cases, in contrast to 9% for PNA and 18% for CNFA interaction with receptors of normal colon mucosa. However, CNFA interacted with over nuclear (but not perіnuсlear) structures of epithelial mucosa of cancer-modified and normal cells, unlike other lectins used in the work. CNFA is considered as N, N'-diacethyllactosediamine specific (GalNAcβ1-4GlcNAc, LacdiNAc). Normally, these receptors are very few common in mammalian cells, but they appear in some cells of tissue of malignant degeneration. However, the applicability of this lectin in the diagnosis isn’t studied enough.The obtained results can be used to develop methods for early diagnosis of malignant tumors of the colon.
Keywords: lectinohistochemistry; colon cancer; diagnostics